Simulation and analysis of ice-induced vibrations experienced but Molikpaq during the May 12, 1986 event - Owen, C.C. (author); Hendrikse, H. (author) (2021)
Much attention has been given to the dynamic ice-structure interaction of the Molikpaq caisson which resulted in severe, almost catastrophic, structural vibrations during the winter of 1985- 1986 at Amauligak I-65 in the Canadian Beaufort Sea. In this study, specific focus is given to the scientific literature describing the ice-induced vibration event on May 12, 1986 over the observed range of ice conditions and drift speeds. While considering the limitations of the measurement data available for the event, the scenario is reviewed and a recent phenomenological model is implemented to simulate the ice-induced vibrations observed. A simplified model of the Molikpaq caisson is simulated to interact with an ice floe and the results are compared with the full-scale observations from the event. Limitations of the modeling with respect to the available full-scale data are discussed and modeling results are compared to previous simulations attempting to explain the event on May 12, 1986. It is concluded that this ice-induced vibration event should be treated with caution and detailed considerations of the scenario, including a comprehensive structural model, must be implemented for accurate simulation of the event on May 12, 1986. Models and theories derived exclusively from this event should be scrutinized in light of its uncertain and complex conditions and thus treated skeptically. Offshore Engineering